U1 small nuclear RNA plays a direct role in the formation of a rev-regulated human immunodeficiency virus env mRNA that remains unspliced. - Lu, X B (1990)
rev-regulated expression of HIV-1 envelope proteins from a simian virus 40 late replacement vector was found to be dependent on the presence of a 5' splice site in the env mRNA in spite of the fact that this mRNA remains unspliced. When the 5' splice site upstream of the env open reading frame was deleted or mutated, expression of envelope protein was lost. RNA analysis of cells transfected with 5' splice-site mutants showed a dramatic reduction in the steady-state levels of env mRNA whether or not rev was present. Envelope expression could be restored in one of the 5' splice-site mutants by cotransfection with a plasmid expressing a suppressor U1 small nuclear RNA containing a compensatory mutation. These experiments show that U1 small nuclear RNA plays a direct and essential role in the formation of an unspliced RNA that is subject to regulation by rev.